(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
Polymers, composites, their components and complexes for application in information tecnologies and biotechnology as well as for medicine and solar energy transfer have been obtained. In particular, new high-resolution photochromic polymer materials with a significant nonlinear optical effect of the third order have been developed. They are perspective for the creation of high-speed optical switches in optical recording and information storage. A new way of recording information based on the generation of the second harmonic with new photochromic polymers has been found. The perspectivity of alken-functionalised poly(phenyl/naphthylmethacrylates) as basic compounds for polarization-sensitive polymeric media was prooved.The chemical modification of polymers by benzenesulfonamide derivatives for biostabilization of plastic masses and providing hydrophilic properties for their surface was carried out. A fundamentally new approach is developed in which processes of energy transfer of excited states in polymer macromolecule to the photostabilaser are used for effective stabilization of polymer materials. Thermostabilized samples of polystyrene with covalently bonded of imidophenylmethacrylates have been developed. The branched copolymers are highly efficient matrices for the synthesis of stable gold, silver, CdS and Au / CdS nanoparticles and copolymers that can be used as nanovectors for the target delivery of highly toxic antitumor drugs. New effective preparations for desinfaсtion of fish nurseries, dressing and hygienic materials, linen and clothes have been developed.